(Be in this world)Analytical Hadith - Azeez , Raad (Islamic Sciences Journal, 2023)
ABSTRACT This study aimed at two axes: The first: to remind our Islamic society of how the educator was The first, which is our master Muhammad, raises the youth to the asceticism of the world in his conversation with Ibn Omar (Be in this world …) which includes gathering of goodness, and the collection of speeches, since the believer should not take from this world a home and should not be attached and assured with it . Rather be like a traveler who carries equipment to the afterlife. The second axis is the study of hadith, an analytical study, which is the study of both support and strneture, and following the original methods of the analytical Hadith.